Dominant ectosymbiotic bacteria of cellulolytic protists in the termite gut also have the potential to digest lignocellulose. (4th August 2015) - Yuki, Masahiro; Kuwahara, Hirokazu; Shintani, Masaki; Izawa, Kazuki; Sato, Tomoyuki; Starns, David; Hongoh, Yuichi; Ohkuma, Moriya
Summary: Wood‐feeding lower termites harbour symbiotic gut protists that support the termite nutritionally by degrading recalcitrant lignocellulose. These protists themselves host specific endo‐ and ectosymbiotic bacteria, functions of which remain largely unknown. Here, we present draft genomes of a dominant, uncultured ectosymbiont belonging to the order B acteroidales, ' Candidatus Symbiothrix dinenymphae', which colonizes the cell surface of the cellulolytic gut protists D inenympha spp. We analysed four single‐cell genomes of C a. S. dinenymphae, the highest genome completeness was estimated to be 81.6–82.3% with a predicted genome size of 4.28–4.31 Mb. The genome retains genes encoding large parts of the amino acid, cofactor and nucleotide biosynthetic pathways. In addition, the genome contains genes encoding various glycoside hydrolases such as endoglucanases and hemicellulases. The genome indicates that C a. S. dinenymphae ferments lignocellulose‐derived monosaccharides to acetate, a major carbon and energy source of the host termite. We suggest that the ectosymbiont digests lignocellulose and provides nutrients to the host termites, and hypothesize that the hydrolytic activity might also function as a pretreatment for the host protist to effectively decompose the crystalline cellulose components.